Possibilities of information technologies to increase quality of educational services in Russia - Igorevna Vaganova, Olga; V. Kamenez, Natalia; Irinia Sergeevna, Vinnikova; Vladimirovna Vovk, Ekaterina; Venediktovna Smirnova, Zhanna; Maseleno, Andino (International Journal of Engineering and Technology, 2018)
The relevance of distance education is the unlimited increase in the opportunities for the society to receive education, as well as the availability of information technology among the younger generation of students. The modern entrant is guided by the availability of an innovative product in an educational institution to which he will give preference. Therefore, the use of distance technologies, development and implementation of online courses in the system of teaching universities is a necessary condition for the success of the university in competition. The article reveals the experience of using online courses at Minin Nizhny Novgorod State Pedagogical University and Tyumen Industrial University. We conducted a formative experiment involving 40 students from Minin Nizhny Novgorod State Pedagogical University. The purpose of the experimental work was to test the effectiveness of the use of information technology developed online course in improving the quality of education of students. There are a lot of advantages of this type of training. Therefore, this article examines the issues of improving educational process by introducing online courses into the learning process that affect the educational process as a whole and also improves the quality of educational services. For market players, this is an opportunity to attract virtually unlimited students, and, consequently, significantly increase profitability. Applying information technologies, developing broadband access to the Internet and its penetration, an online course on the discipline "Service Activities" was created. The developed online course is the only one in the electronic environment of the Pedagogical University, all other courses are designed as an electronic educational and methodical complex. According to experts online learning market in Russia shows an annual growth rate of 25%. At the same time, the volume of Russian market in 2017 is only 10.5 billion rubles, while the world market is estimated at 107 billion dollars. Guided by the results of experimental work, they came to the conclusion that the use of online courses in educational activities in the study of the academic discipline had an interest in independent work, self-examination and self-assessment of knowledge, skills and habits.Â Â